The Performance of Flexible Tip Bougie™ in Intubating Simulated Difficult Airway Model - Mahli, Nurfadilah; Md Zain, Jaafar; Mahdi, Siti Nidzwani Mohamad; Chih Nie, Yeoh; Chian Yong, Liu; Shokri, Ahmad Fairuz Abdul; Maaya, Muhammad (Frontiers in Medicine, 2021)
This prospective, randomized, cross-over study compared the performance of the novel Flexible Tip Bougie™ (FTB) with a conventional bougie as an intubation aid in a simulated difficult airway manikin model among anaesthesiology trainees with regards of first pass success rate, time to intubation, number of attempts and ease of use. Sixty-two anesthesiology trainees, novice to the usage of FTB, participated in this study. Following a video demonstration, each participant performed endotracheal intubation on a manikin standardized to a difficult airway view. Each participant performed direct laryngoscopy and intubated the manikin using a conventional bougie and FTB, at least one day in between devices, in a randomized order. The first pass success rate was significantly higher with FTB (98.4%) compared to conventional bougie (85.5%), p = 0.008. The median time to intubation was significantly faster when using FTB, median = 32.0 sec (Interquartile range [IQR]: 23.8-41.3 sec) compared to when using conventional bougie, median = 41.5 sec (IQR: 31.8-69.5 sec), p < 0.001. The FTB required significantly less intubation attempts compared to conventional bougie, p = 0.024. The overall ease of use, scored on a Likert scale from 1 to 5, was significantly higher in the FTB (4.26 ± 0.53) compared to the conventional bougie (3.19 ± 0.83), p < 0.001. This simulated difficult airway manikin study finding suggested that FTB is a useful adjunct for difficult airway intubation. The FTB offered a higher first pass success rate with a faster time to intubation and less required attempts.